Multimodal classroom interaction analysis using video-based methods of the pedagogical tactic of (un)grouping - Riordan, John-Paul; Revell, Lynn; Bowie, Bob; Hulbert, Sabina; Woolley, Mary; Thomas, Caroline (Pedagogies (Mahwah, N.J.), 2025)
Grouping of people and/or things in school can involve challenging pedagogical problems and is a recurrent issue in research literature. Grouping of pupils sometimes aids learning, but detailed video-based analysis of how teachers (and pupils) group or ungroup (termed '(un)grouping') in classrooms is rare. This multimodal classroom interaction analysis study builds on previous work by exploring how the Pedagogy Analysis Framework can help untangle complicated classroom interactions involving (un)grouping and identifies sixteen types of (un)grouping. The sample size is one class of thirty pupils (10-year-olds), their class teacher, and teaching assistant. Four research methods were used (lesson video analysis, teacher verbal protocols, pupil group verbal protocols, and individual teacher interviews). Six hours of data were video recorded (managed using NVivo). Data were analysed by two educational researchers, the class teacher, and two groups of pupils (three girls and three boys). The methodology is Straussian Grounded Theory. Data were recorded in 2019. We present how often participants (un)grouped during a lesson. We propose and use a grounded theory for (un)grouping which we call the 'Exclusion, Segregation, Integration, and Inclusion (ESII) model'. Additionally, we discuss how misinformation and disinformation can complicate analysis of (un)grouping and examine different perspectives on (un)grouping.